Ova-implantation, embryonic survival and embryonic spacing in ovariectomised mice after progesterone and oestrogen treatment : a thesis presented in partial fulfilment of the requirements for the degree of Master of Veterinary Science at Massey University - Grant, Peter Sutherland (Massey University, 1968)
This investigation is concerned with the ovarian hormonal requirements for ova-implantation, post-implantation survival, and the spacing, of the developing young within the uterus of the ovariectomised pregnant mouse. Most attention is directed towards establishing the effectiveness of the ovarian hormone progesterone in maintaining pregnancy in mice ovariectomised before ova-implantation. Emphasis is placed on the time relationships between the start and interruption of normal pregnancy by ovariectomy. The establishment of continued pregnancy in ovariectomised mice with progesterone treatment then allowed a study of the survival rates and of the spacing of embryos within an altered maternal hormonal environment. Accordingly the thesis presentation is divided into the three sections: I. the ovarian hormonal requirements for ova-implantation; II. the ovarian hormonal requirements for post-implantation survival; III. the ovarian hormonal requirements for embryonic spacing within the uterus. Section I includes a subsection (section I(a)) which deals with the time of ova-implantation in intact mice and a consideration of the health and mating behaviour of the experimental mice. The purpose of this introduction is to provide a general framework on which each of the outlined aspects of reproduction can be more closely examined. [From Introducation]
Keywords: Ovum implantation